Reformasi Korporasi untuk Meningkatkan Tata Kelola Industri Geologi di Era Transisi Energi - Hasan, Nurhaedah; Hasan, Haslindah; Hasan, Muh. Haedar; Hasan, Dina Maliah; Sahudi, Muh. Aksah (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study explores the integration of Environmental, Social, and Governance (ESG) principles and legal compliance in the business models of geology-based companies in Indonesia, emphasizing how profitability aligns with social and environmental responsibility. Using a qualitative normative-empirical approach through legal analysis, company case studies, interviews, and document review, the research finds that embedding ESG into core operations can enhance financial performance, social legitimacy, and legalrisk management when supported by profitability, strong leadership commitment, and clear implementation strategies. However, ESG adoption often remains compliance-driven, constrained by managerial capacity, greenwashing risks, and limited performance indicators linking financial and non-financial outcomes. The study concludes that geological companies should view ESG and CSR regulations as foundations for innovation and long-term competitiveness rather than regulatory burdens, thereby integrating profitability and socio-environmental responsibility within a sustainable business management framework